ANALISIS STRATEGI PEMASARAN DALAM MENINGKATKAN VOLUME PENJUALAN PADA SINAR WAHANA WISATA TOUR & TRAVEL - Halim, Wahyudin; Marpaung , Nicholas (Transpublika Publisher, 2023)
The progress of the tourism sector plays a crucial role in the country's development, and as a result, Travel Bureaus are gaining importance as a support system. These agencies offer tourists invaluable services, but due to the vast potential market, competition is intense. Hence, the objective of this research is to create an appropriate marketing plan that concentrates on Sinar Wihana Wisata Tour & Travel's experience to increase sales volume. According to the findings, the company has implemented effective strategies such as providing various products at different destinations, setting reasonable prices compared to competitors, executing robust promotion schemes, making information accessible to customers, paying attention to employee and tour guide quality, delivering excellent service, and establishing comfortable office facilities. The company's successful strategies include offering diverse product options across various tourist spots, maintaining reasonable prices compared to competitors, deploying aggressive and effective promotion tactics, particularly by leveraging social media platforms such as WhatsApp and Instagram, selecting strategic locations for easy customer access to information, prioritizing excellent customer service, and furnishing offices with comfortable amenities that ultimately boost sales volume.